News of a kidnapping - García Márquez, Gabriel, 1928- (Knopf : Distributed by Random House, Inc., 1997)
This astonishing book by the Nobel laureate Gabriel Garcia Marquez chronicles the 1990 kidnappings of ten Colombian men and women - all journalists but one - by the Medellin drug boss Pablo Escobar. The carefully orchestrated abductions were Escobar's attempt to extort from the government its assurance that he, and other narcotics traffickers, would not be extradited to the United States if they were to surrender.